ANALISIS AKRESI PANTAI DI PANTAI TENGKUYUNG DESA SUNGAI NIBUNG KECAMATAN TELUK PAKEDAI KABUPATEN KUBURAYA - siti fajar; johnny maruli tua sitompul; riyanny pratiwi (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2022)
Tengkuyung Beach has experienced a change in coastline which indicates a forward movement of the coastline, which indicates accretion in the area. Therefore, this study was conducted to find out how much the coastline changes that occurred so that the next steps in the management of coastal areas can be taken. The research method used is quantitative method and qualitative method. The data used include wind, wave, tidal, current and sediment transport data. The results showed that the parameters that caused changes in the coastline were the dominant wind speed from the southwest and northwest, the distance of the breaking waves from the coast, the smaller outflow velocity, the tides and the large sediment transport. Coastal accretion that occurs causes siltation, increased land in the coastal area and reduced the number of fish and shrimp catches. The method used to determine shoreline changes is the Google Earth satellite imagery data processing method and digitizing the coastline using ArcGIS so that the coastline change in 2009 is 0.229 km2, in 2013 is 0.472 km2, 2016 is 0.581 km2 and 2018 is 0.633. km2, while the rate of coastal accretion that occurred in 2009 was 78.957 m, in 2013 it was 83,815 m, in 2016 it was 93,677 m and in 2018 it was 119,663 m which has an additional coastline every year. The concept of countermeasures to overcome the problem of accretion at Tengkuyung Beach is the method of cleaning sediment deposits by dredging. Keywords: Beach Accretion, ArcGIS, Dredging